Synthesis of ferrocene and azobenzene-based copolymers P(FHEMA-co-MAZOHE)s and their redox and photo-responsive properties - Khan, Amin; Yu, Haojie; Wang, Li; Zhizhko, Pavel A.; Zarubin, Dmitry N.; Lemenovskiy, Dmitry A.; Haq, Fazal; Usman, Muhammad; Nazir, Ahsan; Naveed, Kaleem-ur-Rehman (Journal of organometallic chemistry, 2019)
Herein, poly(2-(methacryloyloxy) ethyl ferrocene carboxylate-co-(methacrylohydroxyhexane azobenzene)s) (P(FHEMA-co-MAZOHE)s) were prepared by random copolymerization and were characterized by proton nuclear magnetic resonance (1H NMR) and gel permeation chromatography (GPC) to confirm the structures and molecular weights respectively. Thermal variations were analyzed by thermogravimetric (TG), differential thermogravimetric (DTG) and differential scanning calorimetry (DSC) techniques. Finally, redox and photo stimuli-responsive properties were confirmed by cyclic voltammetry (CV) and ultraviolet–visible spectroscopy (UV–vis) respectively. The results revealed that (P(FHEMA-co-MAZOHE)s) can be useful as information storage materials. [Display omitted] •Ferrocene and azobenzene-based copolymers were synthesized using conventional free radical polymerization.•Photoresponsive behavior was confirmed by UV/vis spectroscopy.•Electroactive behavior was analyzed by Cyclic Voltammetry.•The results indicated that the synthesized copolymers can provide a pathway regarding the four states of information storage.